2010
DOI: 10.1152/ajpheart.01231.2009
|View full text |Cite
|
Sign up to set email alerts
|

Peak systolic velocity of mitral annular longitudinal movement measured by pulsed tissue Doppler imaging as an index of global left ventricular contractility

Abstract: Seo JS, Kim DH, Kim WJ, Song JM, Kang DH, Song JK. Peak systolic velocity of mitral annular longitudinal movement measured by pulsed tissue Doppler imaging as an index of global left ventricular contractility. Am J Physiol Heart Circ Physiol 298: H1608 -H1615, 2010. First published March 5, 2010; doi:10.1152/ajpheart.01231.2009.-We sought to test whether the peak systolic velocity of mitral annular longitudinal movement (S=) measured by pulsed tissue Doppler imaging technique is useful to assess global left ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 36 publications
3
37
0
Order By: Relevance
“…Sa is the peak myocardial tissue Doppler velocity during systole and Ea is the peak myocardial tissue Doppler relaxation velocity during early diastole (Figures 4A,B). Sa 17 is analogous to (+dP/dt) max and Ea 18 is analogous to (−dP/dt) min ; therefore, Sa, Ea, and Ea/Sa are in vivo analogues of (+dF/dt) max , (−dF/dt) min , and |(−dF/dt) min |/(+dF/dt) max measurements in papillary muscles. cMyBP-C(t3SA) hearts exhibited depressed Sa, Ea, and Ea/Sa (Figure 4C,D), providing an in vivo correlate to the depressed twitch kinetics observed in papillary muscles.…”
Section: Resultsmentioning
confidence: 89%
“…Sa is the peak myocardial tissue Doppler velocity during systole and Ea is the peak myocardial tissue Doppler relaxation velocity during early diastole (Figures 4A,B). Sa 17 is analogous to (+dP/dt) max and Ea 18 is analogous to (−dP/dt) min ; therefore, Sa, Ea, and Ea/Sa are in vivo analogues of (+dF/dt) max , (−dF/dt) min , and |(−dF/dt) min |/(+dF/dt) max measurements in papillary muscles. cMyBP-C(t3SA) hearts exhibited depressed Sa, Ea, and Ea/Sa (Figure 4C,D), providing an in vivo correlate to the depressed twitch kinetics observed in papillary muscles.…”
Section: Resultsmentioning
confidence: 89%
“…Similarly our study patients also showed an improvement in LV function as assessed by ejection fraction. Peak Mitral velocities [2] are exhibiting stable (normal) behavior with respect to all the 4 conditions (control & study). So, this echo parameter can be used to follow the cases in clinical practice to know the improvement in LV contractility like standard EF.…”
Section: Discussionmentioning
confidence: 91%
“…We also assessed the effect of afterload on S', which is influenced by the time-varying interaction between LV contractility and afterload during systole. Recently, S' was shown to be influenced by myocardial contractility (even in the presence of a normal ejection fraction), longitudinal fiber shortening, and torsional deformation, 13 and to be an independent predictor of mortality in a general population sample with normal LV ejection fraction. 14 In addition to S', we also assessed average longitudinal strain using speckle-tracking echocardiography as described below.…”
Section: Central Pressure and Echocardiographic Measurementsmentioning
confidence: 99%